2020
DOI: 10.3390/microorganisms8030415
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Therapeutic Drug Monitoring of Colistin in Critically Ill Patients Reveals Undetected Risks

Abstract: (1) Background: With the rise of multi-/pan-drug resistant (MDR/PDR) pathogens, the less utilized antibiotic Colistin has made a comeback. Colistin fell out of favor due to its small therapeutic range and high potential for toxicity. Today, it is used again as a last resort substance in treating MDR/PDR pathogens. Although new guidelines with detailed recommendations for Colistin dosing are available, finding the right dose in critically ill patients with renal failure remains difficult. Here, we evaluate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…4,30 Previous pharmacokinetic studies have reported large variations in the t ½ of colistin in critically ill patients with mean values ranging from 1.6 to 22 hours. 9,25,33 The t ½ of colistin found in our study, that is 2.99 ± 0.43 hours, is consistent with previous reports. 21,28 Variability in the V d and CL was determined to be accountable for the heterogenicity in the t ½ of colistin.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…4,30 Previous pharmacokinetic studies have reported large variations in the t ½ of colistin in critically ill patients with mean values ranging from 1.6 to 22 hours. 9,25,33 The t ½ of colistin found in our study, that is 2.99 ± 0.43 hours, is consistent with previous reports. 21,28 Variability in the V d and CL was determined to be accountable for the heterogenicity in the t ½ of colistin.…”
Section: Discussionsupporting
confidence: 93%
“…The terminal half-life of colistin varies widely and values between 1.6 and 22 hours. 33 The differences in the terminal half-lives observed in previous studies primarily arise from the differences in the V d , which is widely altered by pathophysiological changes occurring in critically ill patients. 28 Also, studies describing a longer terminal half-life of colistin, that is >6 hours, have a rapid workup procedure following sampling, thereby reducing ex vivo conversion of CMS to colistin.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The authors evaluated the efficiency of the current guidelines’ recommendations by using high resolution therapeutic drug monitoring of colistin. The authors analyzed plasma levels of colistin and its pro-drug colisthimethate sodium (CMS) in 779 samples, drawn from eight intensive care unit (ICU) patients with pan-drug resistant (PDR) infections [ 6 ]. This study found that CMS levels did not correlate with colistin levels and over- or under-dosing occurred regardless of renal function and the mode of renal replacement therapy, while colistin elimination half-time appeared to be longer than previously reported [ 6 ].…”
mentioning
confidence: 99%